(untitled)
Impaired lipid metabolism in diabetic patients can lead to cardiovascular complications. Poor glycaemic control is associated with a significant increase in the risk of both patient’s morbidity and mortality. An early intervention to regulate circulating lipids has been found to lower the risk of cardiovascular problems and death. Glycated hemoglobin (HbA1c) is a reliable indicator of rising blood sugar levels. This hospital based observational study was conducted in the Department of Medicine, Sher-E-Bangla Medical College Hospital, Barisal from October 2014 to March 2015 over a period of 6 month to determine the correlation of glycemic control and lipid profile in patients with type 2 diabetes. A total of 110 type 2 diabe- tes mellitus(DM) patients of both sexes admitted to the Deapartment of Medicine of Sher-E- Bangla Medical College Hospital, Barisal, were recruited for this study. Following standard procedures and protocols, fasting blood sugar (FBS), blood sugar two hours after breakfast, Glycosylated Hemoglobin (HbA1c) and fasting lipid profile were measured. The age of respondents ranged from 34 to 70 years with the mean age of 54.35